Ventricular asystole in a CRT‐D device. What is the mechanism?. Issue 9 (16th August 2019) - Reddy, Pavan; Do, Khuyen; Doshi, Rahul; Shinbane, Jerold; Konecny, Tomas
Abstract: We present a case of an 89‐year‐old man with a left ventricular assist device and cardiac resynchronization therapy device (CRT‐D) who presented with multiple presyncopal events. On the night of admission, telemetry revealed a 13‐s pause with appropriately timed pacing spikes but with failure to capture, followed by intermittent ventricular contraction with different QRS morphology. What was the mechanism for his ventricular asystole?